THE PREVALENCE OF DEPRESSION AMONG ELDERLY IN RURAL COMMUNITY AREA OF SOUTHERN PERAK - Rosilah Wahab,; Siti Nur Atikah Nor Azni,; Mohammad Ghazali Masuri, (Journal of Islamic, Social, Economics and Development, 2021)
Geriatric depressive disorder is a major public health concern around the world,contributing to increasing healthcare costs and mortality. Depression is commonly found inelderly, thus primary care provider should be vigilant when treating elderly patient. Theincrease prevalence of depression in Asia among elderly and the clear association betweendepression and old age suicide need to give attention, prevention and intervention. This studydesired to determine the prevalence of depression among elderly in rural community area ofsouthern Perak. 283 participant was involved in this study. Geriatric Depression Scale MalayVersion (GDS- M-14) was used to measure the prevalence of depression among participant.The result of this study showed that there is significant association between age and total scoreof Geriatric Depression Scale ( GDS ) ( p= 0.002 ). This study also showed that there is perfectsignificant correlation between living arrangement and total score of Geriatric DepressionScale ( GDS ) ( p< 0.01 ). There is no significant difference in total score Geriatric DepressionScore (GDS) with age group and marital status group since the p > 0.05. There is a significantrelationship between gender male and female with a total score of Geriatric Depression Scale( GDS ). The research findings will give awareness for Ministry of Health focusing on theimprovement of service and facilities that affect the well-being of elderly persons and othercommunity members, including health care service, technology, social supports, and manymore. Thus it will also be promoting for comprehensive ageing in place concept.